Comparative study of codecombat-based python programming and scratch programming effects on sixth graders' Computational thinking: interaction effects of gender and programming experience - Sun, Lihui; Liu, Junjie (Thinking skills and creativity, 2025)
•CodeCombat-based Python and Scratch programming activities significantly enhance 6th graders’ CT.•Long-term CodeCombat-based Python activities had more significant effects on students’ CT.•Scratch programming removes the impact caused by programming experience.•CodeCombat-based Python programming facilitates CT gains for students with programming experience.•Gender and programming experience have interaction effects in CodeCombat-based Python programming. Text-based Python and block-based Scratch programming have received significant attention in primary school computational thinking (CT) education. However, few studies have compared the differences between CodeCombat-based Python and Scratch programming approaches and knowledge of their relative effectiveness is lacking. This study aimed to explore differences in the impact of CodeCombat-based Python and Scratch programming on sixth grade students’ CT. The influence of students’ gender and programming experience was also considered. Therefore, we conducted an 11-week quasi-experimental study with 87 students. They were divided into two groups to participate in CodeCombat-based Python and Scratch programming teaching activities respectively. The results showed that both CodeCombat-based Python and Scratch programming activities significantly improved students’ CT skills, but Python programming had more effective and sustained effects on students' CT development. We also found that Scratch programming eliminated differences in CT from programming experience. In contrast, CodeCombat-based Python programming amplified the influence of programming experience and benefitted the CT development of students with programming experience. More interestingly, there was no gender difference in students’ CT in the Python group, but there were significant interaction effects between gender and programming experience. We found that girls with programming experience improved significantly more in CT than boys with programming experience, breaking gender stereotypes in CT. This study enriches researchers’ and frontline teachers’ understanding of CodeCombat-based Python and Scratch programming and provides empirical evidence for future teaching approach choices.